Penerapan Model Blended Learning Berbasis Lembar Kerja Untuk MeningkatkanMotivasi Dan Hasil Belajar Matematika Siswa Kelas VIII - Baiq Puspa Erlian; Muhamad Akrom (Lembaga Einstein College, 2023)
The main objective of this Classroom Action Research is to increase motivation and learning outcomes in Mathematicsregarding Relations and Functions through the application of a worksheet-based blended learning model. Learning motivationdata was collected using questionnaires, while learning outcomes data was collected using test and assignment techniques.Learning motivation data was analyzed descriptively narratively and learning outcome data was analyzed quantitatively bydetermining the mean, frequency, range and percentage of classical completeness. The results of the research show that thereis an increase in motivation and learning outcomes in each cycle, from the initial/pre-cycle conditions, the learning conditionswere very passive with classical completeness only 11.76% (knowledge aspect) and 23.53% (skills aspect), increasing to32.35% of students had high motivation with classical completeness of 26.47% (knowledge aspect) and 43.33% (skills aspect)in cycle I, and increased again in cycle II to 50% of students had high motivation with classical completeness of 55.88%(knowledge aspect) and 70% ( skill aspect). In line with the research results, it was concluded that the application of theworksheet-based blended learning model could increase motivation and learning outcomes in Mathematics regardingrelations and functions in class VIIIG students at MTs Muallimat NW Pancor for the 2022/2023 academic year. Thesuggestions proposed are mainly for teachers to further optimize the learning process through implementing a blendedlearning model adapted to the material and conditions in order to provide a more meaningful learning experience.